Oracle SQL Recipes A Problem-Solution Approach - Allen, Grant; Bryla, Bob; Kuhn, Darl; Allen, Chris (Apress : Imprint: Apress, 2009)
Have you ever been faced with a new type of query to write, or been asked to create an unfamiliar database object? In such situations, you have probably wanted a good, solid example upon which to build, and instead have been forced into the drudgery of parsing railroad-style syntax diagrams in Oracle's manual set. This book frees you from that drudgery by providing tested and working examples of SQL used to solve common problems faced by developers and database administrators on a daily basis. When you're under pressure to get results fast, Oracle SQL Recipes is there at your side. Example-based, providing quality solutions to everyday problems Respects your time by putting solutions first and keeping discussions short Solves the most commonly encountered SQL problems.